2014
DOI: 10.3892/or.2014.3536
|View full text |Cite
|
Sign up to set email alerts
|

Activation of STAT3 is involved in malignancy mediated by CXCL12-CXCR4 signaling in human breast cancer

Abstract: The chemokine receptor CXCR4 and signal transducer and activator of transcription 3 (STAT3) play an important role in breast cancer malignancy and metastasis. However, it remains unknown whether STAT3 can be activated by CXCR4 in human breast cancer. The expression levels of CXCR4, STAT3 and p-STAT3 in 208 breast cancer tissues and 26 tumor-adjacent tissues were examined by immunohistochemistry. Flow cytometry, western blot analysis and immunoprecipitation were used to study activation of STAT3 by CXCL12-CXCR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Inhibition of CXCR4 and the tumor-stromal cross-talk by HNK can have big implications because of the documented role of CXCR4/CXCR12 signaling in cancer metastasis (33) and drug resistance (14,34). Activation of this signaling axis induces diverse signaling pathways that act independently and cross-talk with each other and/or other active signaling pathways to promote a variety of cancer-relevant cellular and molecular responses (16,35). Besides, we also observed an inhibition of SHH expression by HNK, which is highly relevant to tumor-stromal interactions (13,15,25).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CXCR4 and the tumor-stromal cross-talk by HNK can have big implications because of the documented role of CXCR4/CXCR12 signaling in cancer metastasis (33) and drug resistance (14,34). Activation of this signaling axis induces diverse signaling pathways that act independently and cross-talk with each other and/or other active signaling pathways to promote a variety of cancer-relevant cellular and molecular responses (16,35). Besides, we also observed an inhibition of SHH expression by HNK, which is highly relevant to tumor-stromal interactions (13,15,25).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant STAT3 signaling promotes initiation and progression of human cancers by either inhibiting apoptosis or inducing cell proliferation, angiogenesis, invasion, and metastasis. It has been reported that CXCR4 signaling activates the JAK2/STAT3 pathway in many types of cancers (36,37). To elucidate the signaling pathways underlying sinomenine-mediated responses in osteosarcoma cells, we further investigated the effects of sinomenine on CXCR4 and STAT3 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al analyzed 208 breast cancer tissues, and they noticed high level of STAT3 immunoreactivity in 72% (n=150) of cancer samples; whereas high p-STAT3 expression was present in 43.8% (n=91) cases [63]. The expression levels of both STAT3 and p-STAT3 were increased with higher TNM stage and lymph node metastasis.…”
Section: Leptin Biology and Molecules Of Relevant Signal Transductmentioning
confidence: 99%